Pharmacovigilance on cannabidiol as an antiepileptic agent - Ammendolia, Ilaria; Mannucci, Carmen; Cardia, Luigi; Calapai, Gioacchino; Gangemi, Sebastiano; Esposito, Emanuela; Calapai, Fabrizio (Frontiers in Pharmacology, 2023)
Introduction: Cannabidiol (CBD) is an active chemical contained in the plant Cannabis sativa. It is a resorcinol-based compound that crosses the blood-brain barrier without causing euphoric effects. CBD has a plethora of pharmacological effects of therapeutic interest. CBD has been authorized in the European Union as an anticonvulsant against serious infantile epileptic syndromes, but its safety profile is still not sufficiently described. Methods: With the goal of expanding information on the safety of CBD use as an antiepileptic agent beyond the most common side effects known through clinical studies, an analysis of serious case reports on suspected adverse reactions (SARs) to CBD licensed as an anti-epileptic drug found in the EudraVigilance database is reported in this article. EudraVigilance is a system purchased by the European Medicines Agency (EMA) for monitoring the safety of medicinal products marketed in Europe. Results: The most frequent serious SARs to CBD in EudraVigilance were epilepsy aggravation, hepatic disorders, lack of efficacy, and somnolence. Discussion: Based on our analysis, the following precautions should be adopted for appropriate monitoring of potential adverse effects, more attention towards possible CBD medical use as an antiepileptic: awareness of interactions with other drugs, epilepsy aggravation, and drug effectiveness.